Letter - Frank, W.
012a-0080-001 S.I.A SOLIDARIDAD INTERNACIONAL ANTIFASCISTA (International Anti-Fascist Solidarity) Sponsors— Mr W. H. AUDEN Mr C.E.M. JOAD Sir THOMAS BURKE Mr MILES MALLESON Dr STELLA CHURCHILL Mr GEORGE ORWELL Miss NANCY CUNARD Dr G V PEARSON Mr HAVELOCK ELLIS Mr JOHN COWPER POWYS Mr LOUIS GOLDING Mr LLEWELYN POWYS Miss SIDONIE GOOSSENS Mr HERBERT READ Mr LAURENCE HOUSMAN Mr REGINALD REYNOLDS Mr BRIAN HOWARD Miss REBECCA WEST Rev JAMES WHITTLE Telephone: GERard 2636 ETHEL MANNIN Hon. Treasurer EMMA GOLDMAN Hon. Secretary London Office 21, FRITH STREET, SHAFTESBURY AVENUE, LONDON. W.1. Dear Mr. Wray, I am writing you in the interest of the documentary film, "Dawn in Spain", just received from Barcelona. The first private showing was attended by representatives of parliament and various Labour organisations, among whom were Mr. McGovern, M.P., Miss Monica Whately, Mr Frederick J. Warburg, Mr. Miles Malleson and Mr. Willis, Secretary of the London Trades Council. Everyone present expressed deep appreciation of the excellent portrayal of the real motives of the Spanish tragedy and its consequences. The film deals not only with the war in Spain, but with the very fine constructive work which is being carried on by the Spanish people, united in a common effort to win their independance against all obstacles. For your guidance, we are planning to show the film to the entire House of Commons at an early date. I should be pleased to have your suggestions as to your possible collaboration in bringing this film before your organisation. Yours sincerely, W. Frank Director. 292/946/12a/80